2021
DOI: 10.2196/preprints.28661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Listening to Stakeholders Involved in Speech-Language Therapy for Children With Communication Disorders: Content Analysis of Apple App Store Reviews (Preprint)

Abstract: BACKGROUND With the plethora of mobile applications (apps) available in the App Store, more speech-language pathologists (SLPs) have adopted apps for speech-language therapy services, especially for pediatric clients who may benefit from various interactive apps. App Store reviews are publically available data sources that can not only create avenues for communication between technology developers and consumers to understand user needs and challenges but also inform and educate clinicia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Usability studies provide valuable insights into how mental health apps can better meet the needs of diverse users. Studies have found that aspects like user engagement, partic-ipatory design, user-centred design, and the inclusion of end-users in the evaluation process are critical for mental health app effectiveness [37][38][39][40] . The usability of mental health apps has also been linked to their impact on specific mental health conditions 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Usability studies provide valuable insights into how mental health apps can better meet the needs of diverse users. Studies have found that aspects like user engagement, partic-ipatory design, user-centred design, and the inclusion of end-users in the evaluation process are critical for mental health app effectiveness [37][38][39][40] . The usability of mental health apps has also been linked to their impact on specific mental health conditions 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Usability studies provide valuable insights into how mental health apps can better meet the needs of diverse users. Studies have found that aspects like user engagement, participatory design, user-centred design, and the inclusion of end-users in the evaluation process are critical for mental health app effectiveness [38][39][40][41] . The usability of mental health apps has also been linked to their impact on specific mental health conditions 42,43 .…”
Section: Introductionmentioning
confidence: 99%